Comparison the Posterior Shell and Posterior Leaf Spring Socket Design for Syme’s Amputee in Terms of Normal Gait Kinematics: Case Study - Shah, Wisal; Uzma, Bibi; Khan, Muhammad Kamran (Journal of Prosthetics Orthotics and Science Technology, 2023)
Background: Syme’s amputee patient commonly walks on the distal end of the stump. Two types of sockets are commonly prescribed to these patients; Syme socket with either complete posterior shell or leaf spring design. The purpose of this kinematic study was to compare the effectiveness of both these socket designs in terms of different gait variables. Methods: The study design was a case study, therefore, only a single syme’s amputee was selected for data collection. Both posterior shell and posterior leaf spring sockets were made for the study participant. The study participant was given the opportunity to use each socket for 15 days before data collection in 2D gait analysis lab. The data was compared with normal gait values, so the socket which had gait parameter values was closer to the normal gait kinematic values. That was considered as the most effective socket. Results: The results of this study showed that the posterior leaf spring socket design has closer to normal Stance phase (62%) as compared to complete posterior shell design (65%). Similarly, the values of swing phase were 38% for leaf spring design and 35% for posterior shell design which clearly indicate that the posterior leaf spring socket design is more effective than posterior shell socket design.